2013
DOI: 10.1039/c2nr33146b
|View full text |Cite
|
Sign up to set email alerts
|

Direct electrochemical detection and sizing of silver nanoparticles in seawater media

Abstract: We report proof-of-concept measurements relating to the impact of nanoparticles with an electrode potentiostatted at a value corresponding to the diffusion controlled oxidation of silver nanoparticles in authentic seawater media. The charge associated with the oxidation reveals the number of atoms in the nanoparticle and thus its size and state of aggregation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
83
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(84 citation statements)
references
References 18 publications
1
83
0
Order By: Relevance
“…4−6 Typically, Ag NPs are expected to have a low environmental persistence, as dissolution or agglomeration/aggregation and subsequent sedimentation is assumed to occur on relatively short time scales. 7 However, recent successful efforts to stabilize NPs in complex suspensions, especially those of high ionic strength, such as cell environments, 8 seawater, 9 blood, 10 and stomach acid, 11 will result in increased environmental persistence and a greater opportunity for the uptake of nanosilver into biological systems. The stability of the NP is governed largely by the choice of the capping agent, 12 which is added to prevent aggregation and agglomeration of the nanoparticles.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4−6 Typically, Ag NPs are expected to have a low environmental persistence, as dissolution or agglomeration/aggregation and subsequent sedimentation is assumed to occur on relatively short time scales. 7 However, recent successful efforts to stabilize NPs in complex suspensions, especially those of high ionic strength, such as cell environments, 8 seawater, 9 blood, 10 and stomach acid, 11 will result in increased environmental persistence and a greater opportunity for the uptake of nanosilver into biological systems. The stability of the NP is governed largely by the choice of the capping agent, 12 which is added to prevent aggregation and agglomeration of the nanoparticles.…”
Section: ■ Introductionmentioning
confidence: 99%
“…9 A recent publication by Toh et al 17 observed reactivity differences of NPs in water, but no new insight into the dynamics of the different capping agents in that aqueous medium was gained. To examine the effect of the capping agent on the particle−solution dynamics, extending existing approaches to examine NPs in an entirely different, high-ionic strength solvent such as room-temperature ionic liquids (RTILs) is highly advantageous.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The collisions of these particulates with an electrode at a positive potential bias 15 have resulted in spikes from impact electrochemistry. These electrochemical signals find their origins from the electrochemical oxidation reactions that occur.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The same authors have studied the evolution of silver nanoparticles in seawater using Ag NP standards and they found that silver nanoparticles were aggregated in this media over the time scale of the measurements [207]. To date, applications involve metallic nanoparticles and anodic PCC, whereas cathodic PCC has just been used for the characterization of pristine nanomaterials, like magnetic nanoparticles of Fe 3 O 4 [208].…”
Section: By Using Vip Size and Mass Concentration Of Silver Nanopartmentioning
confidence: 99%